How to define an Skinnerian? A reflexion upon teachers, disciples and intelectual influence - De Rose, Júlio César (Brazilian Journal of Behavioral and Cognitive Therapy, 1999)
Thinkers and scholars of psychology tipically belong to a school of thought, an "approach". This article analyses the influence of great thinkers on the formation of a school of thought, and the need of both convergent and divergent disciples for the fertility of the master’s thought. The article analyses, in these terms, the influence of Skinner, concluding that he has had important convergent disciples and pratically no divergent disciple. This may limit the variability of skinnerian thought and ultimately compromise the fertility and even the survival of skinnerian thought.